Different effect of nitrogen sources in autotrophic and mixotrophic culture of Scenedesmus spfor biomass and carotenoids production using acidic coal mine drainage effluents (2021)
In the present study, the conditions for an autotrophic and mixotrophic culture of Scenedesmus sp were established. Effluents from acidic coal mine drains were used to study biomass and carotenoid production, both under autotrophic and mixotrophic conditions in relation to the effect of different sources of nitrogen: sodium nitrate, urea and ammonium phosphate. Pollutant removal was determined, such as COD, TOC, heavy metals, ions and total suspended solids. Batch cultures lasted nine days and biomass production, carotenoids and pollutant removal were compared in each condition. The highest biomass concentration reached was 1.2 g/L in the mixotrophic culture with urea, followed by the culture with sodium nitrate of 0.9 g/L in a C/N ratio of 6:1. The highest carotenoid specific concentration was reached in the mixotrophic culture with sodium nitrate, 19.43 mg carotenoids /g biomass. The culture with ammonium phosphate was found to be inhibitory for the growth of the microalgae with the lowest results of all the parameters except for the autotrophic culture where the concentration of carotenoids was very similar to those reached with sodium nitrate and urea. Finally, the mixotrophic culture with urea presented the highest removal percentages, being 86.97% for total iron, 58.29% for chlorides and 92.5% for COD.